1991
DOI: 10.1111/j.1530-0277.1991.tb00615.x
|View full text |Cite
|
Sign up to set email alerts
|

Macrocytosis as a Consequence of Alcohol Abuse among Patients in General Practice

Abstract: Macrocytosis, a common finding in patients without anemia or other hematologic abnormalities, is often ignored. The purpose of this prospective study was to investigate 300 consecutive, adult health-center patients with a mean cell volume (MCV) value greater than or equal to 100 fl. The incidence of macrocytosis was 2.4%. Of the 177 male and 123 female patients, only 14 (4.7%) were anemic; 80.2% of the men (89.3% of those under 60 years) and 34.1% of the women were alcohol abusers, representing the largest dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…Although 37 patients (34 %) were daily alcohol drinkers, the authors argued that alcoholism alone is not sufficient to raise MCV above 130 fL. This was consistent with our data and those of previous reports: Seppä et al reported that the highest MCV value found in alcoholics without folate or vitamin B12 deficiency was 120 fL [22], and Veda reported that the maximum MCV observed in alcoholism was 114 fL [16]. Regarding the effect of medications, in our series as in previous reports, one patient treated with HU showed an MCV of 130.2 fL, and one patient among those seen at the eight other hospitals showed an MCV of 133.5 fL.…”
Section: Discussionsupporting
confidence: 95%
“…Although 37 patients (34 %) were daily alcohol drinkers, the authors argued that alcoholism alone is not sufficient to raise MCV above 130 fL. This was consistent with our data and those of previous reports: Seppä et al reported that the highest MCV value found in alcoholics without folate or vitamin B12 deficiency was 120 fL [22], and Veda reported that the maximum MCV observed in alcoholism was 114 fL [16]. Regarding the effect of medications, in our series as in previous reports, one patient treated with HU showed an MCV of 130.2 fL, and one patient among those seen at the eight other hospitals showed an MCV of 133.5 fL.…”
Section: Discussionsupporting
confidence: 95%
“…MCV has long been used as part of the screening procedure for detecting alcohol abuse 11 . An elevation of MCV in AD patients may be caused by a deficiency of folate or vitamin B12 or as a direct result of exposure to ethanol per se or its metabolite (i.e., acetaldehyde).The significantly higher value of MCV in AD patients compared to healthy controls seen in this study is in agreement with previous studies [12][13] .The association of MCV with amount of alcohol consumed indicates a dose dependent pattern. Thus heavy chronic users may report a higher MCV levels as compared to moderate users.…”
Section: Resultssupporting
confidence: 91%
“…However, looking at macrocytosis in the studied population, 24 patients (4.7%) revealed pathologic values of [100 fl. Comparing these with the cumulative macrocytosis values from literature (480/ 16,488; 2.9%) consisting of 1.7% [11], 2.4% [12], 3.0% [7], 3.7% (cut off 98.5 fl) [13] we observed a significantly higher incidence (p = 0.03). Twelve of the 24 patients (50%) had a bleeding source located posteriorly and (Fig.…”
Section: Resultssupporting
confidence: 46%